Determination of Waste Processing Options to Extend Landfill Service Life - Murwan Widyantoro; Suprihatin Suprihatin; Nastiti Siswi Indrasti; Tajuddin Bantacut (Poltekkes Kemenkes Surabaya, 2026)
Waste reduction and handling in landfills is still a problem. Waste that accumulates in landfills can threaten the life and capacity of the landfill. Therefore, waste processing in landfills must be resolved properly to reduce the negative impacts it causes. This study aims to choose the best scenario option for processing organic waste, especially food waste, so that it can prolong the landfill's lifespan. The research location is at Galuga Landfill because it has a food waste composition of Bogor City's total garbage production weight. The method used is Material Flow Analysis (MFA). The study's results indicated that Scenario 1 resulted in 40% of organic waste being sent to landfills, which extended the landfill's lifespan by 8 years. In contrast, Scenario 2 produced 35% of organic waste destined for landfills, adding 10 years to the landfill's lifespan. The last scenario 3 was 8% with the landfill age being 16 years longer. In conclusion, this study finds that scenario 3 is the most promising option. It not only generates products with high economic value but also helps to extend the lifespan of the landfill compared to other scenarios.